PREVENTION MEASURES OF HEPATITIS B IN HEALTHCARE INSTITUTIONS FROM THE PERSPECTIVE OF THE NURSING SCOPE OF WORK - Brnovic, Dragana; Pelicic, Damir (Sanamed, 2024)
Viral hepatitis B (hepatitis B) poses a significant public health challenge on a global scale, particularly affecting populations in middle- and low-income countries, including those in the developing world. It primarily impacts individuals engaging in risky behavior and healthcare workers directly or indirectly involved in providing services to these patients.This paper will present information from pertinent professional and scientific sources on hepatitis B, preventive measures, and the role of nurses in their implementation. This review paper is a valuable contribution, providing recommendations and insights derived from the professional practice of nurses across all levels of healthcare.
Keywords: infection; preventive measures; healthcare; intrahospital hepatitis B infections